Flexible Hall sensors based on graphene. Issue 14 (21st March 2016) - Wang, Zhenxing; Shaygan, Mehrdad; Otto, Martin; Schall, Daniel; Neumaier, Daniel
Abstract : Fully flexible and ultrathin Hall sensor based on graphene with high sensitivity for magnetic field detection and stability under bending. Abstract : The excellent electronic and mechanical properties of graphene provide a perfect basis for high performance flexible electronic and sensor devices. Here, we present the fabrication and characterization of flexible graphene based Hall sensors. The Hall sensors are fabricated on 50 μm thick flexible Kapton foil using large scale graphene grown by chemical vapor deposition technique on copper foil. Voltage and current normalized sensitivities of up to 0.096 V VT −1 and 79 V AT −1 were measured, respectively. These values are comparable to the sensitivity of rigid silicon based Hall sensors and are the highest values reported so far for any flexible Hall sensor devices. The sensitivity of the Hall sensor shows no degradation after being bent to a minimum radius of 4 mm, which corresponds to a tensile strain of 0.6%, and after 1000 bending cycles to a radius of 5 mm.